Pembelajaran Anak Usia Dini dengan Pendekatan Proyek - Martha Christianti (Dinamika Pendidikan, 2011)
Project  approach  is one approach that combines the principles  of early childhood learning that is playing while learning and child-centered learning. In this approach, the emphasis on the application of learning skills; the  child's  motivation  to  learn appears to  be  intrinsically  rather  than extrinsically; interest and involvement of children increased effort and motivation to find  out about something not because of the necessity of a teacher or wish to obtain a specific reward; children are given the freedom to choose activities that have been provided and tried to find  answers to the challenges of a more appropriate rathe~ than the dominance of the teacher in selecting learning activities, providing :teachingmaterials at the appropriate level of teaching; child is proficient, the teacher helps develop the skills that exist in the child, not the teacher as expert view children as individuals who have weaknesses, and children share responsibility with teachersfor  learning and  achievement  rather  than  teachers are  responsible for   learning  and achievement  is  a  necessity  that  must; be  achieved  by  the  children.  This approach is to develop all aspects of t~e development of religious and moral values, physical, cognitive, language, social and emotional in an integrated, not separated (fragmented).   Key word: Project al!proach,playing while learning, child-centered